Rare Cause for Sudden Right Heart Failure. (2010) - Nia, Amir M.; Gassanov, Natig; Schmidt, Matthias; Kuhn-Régnier, Ferdinand; Erdmann, Erland; Er, Fikret
Abstract : Right heart failure occurs daily in clinical settings, but an underlying cardiac malignant tumor is very uncommon. We report a case of a 48-year-old man presenting only with palpitations and decompensated heart failure. Echocardiographic imaging revealed a large tumor of the right ventricle. Shortly after a putatively successful surgical approach, the patient was admitted again with heart failure symptoms. On reassessment, a complete relapse with multiple metastases could be seen. Generally, cardiac malignant tumors are diagnosed at a time-point when therapeutic options are very limited or even postmortem. Broad echocardiographic screening in patients with unspecific symptoms might be helpful to detect cardiac malignant tumors at early stages.